(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the archaeological research of the Jarqo‘ton site and the Tozabog‘yo‘p culture. Additionally, it highlights the development of urban planning, metallurgy, pottery, and agriculture in Central Asia during the Bronze Age, as well as the economic, cultural, and religious life of society.